PENGARUH MELUKIS TARIK BENANG TERHADAP PERKEMBANGANKREATIVITAS ANAK DI TAMAN KANAK-KANAK YARI SCHOOL - Shinta Permata Zekri; Farida Mayar; Nenny Mahyuddin; Mutia Afnida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of string-pull painting activities on the development of children's creativity at Yari School Kindergarten. Based on initial observations, it was found that most children had low interest in exploring colors and shapes. Some children were seen merely imitating their friends’ works without showing unique creativity. In addition, the children tended to get bored quickly and were less actively engaged in the painting process. Some of them also experienced difficulties in combining colors and creating varied patterns. Therefore, one of the strategies that can be used is to examine the effect of string-pull painting on the development of children's creativity. The research method used was a quantitative approach with a pre-experimental design. The form of pre-experimental design employed was the one-group pretest-posttest design. The sampling technique used was purposive sampling, with class B2 serving as the experimental class. Based on the normality test results, the pre-test data obtained a significance value of 0.231 > 0.05, indicating that the pre-test experimental data were normally distributed. The homogeneity test showed a Levene’s test of variance significance value of 0.943 > 0.05, indicating that the N-Gain variance for the pretest and posttest experimental data was equal or homogeneous. Furthermore, the hypothesis test using the independent sample t-test resulted in a significance value (2-tailed) of 0.000 < 0.05, meaning there was a significant difference between the pre-test and post-test results. This indicates that string-pull painting has an effect on the development of children's creativity at Yari School Kindergarten.